2023
DOI: 10.1111/bph.16092
|View full text |Cite
|
Sign up to set email alerts
|

A positive TGF‐β/miR‐9 regulatory loop promotes the expansion and activity of tumour‐initiating cells in breast cancer

Abstract: Background and Purpose: MicroRNA-9 (miR-9) has previously been described as a dual-functional RNA during breast cancer progression and its roles need to be clarified thoroughly.Experimental Approach: A miR-9 knockout mode of mouse breast cancer, the MMTV-PyMT model (PyMT-miR-9 À/À ), combined with different human breast cancer cell lines were used to evaluate the effects of miR-9 on breast cancer initiation, progression and metastasis. Lin-NECs (Neoplastic mammary epithelial cells) and pNECs (Pre-neoplastic ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…Its role is well established in BC as well, where it acts as a tumor suppressor gene [ 211 ], regulates cell motility and invasion [ 212 ], endothelial differentiation [ 103 ], metastasis formation [ 213 , 214 ], cell migration [ 215 ], and apoptosis [ 216 ]. It has also been shown that STARD13 exerts its function in BC through its participation in many ceRNETs, such as the one involving a positive TGF-β/miR-9 regulatory loop mediated by the STARD13/YAP axis [ 217 ], the one involving hsa-miR-21-3p [ 218 ], or even the more complex network that involves five different miRs and that controls YAP/TAZ nuclear accumulation and transcriptional activity via modulation of Hippo and Rho-GTPase/F-actin signaling pathways [ 219 ]. A direct link between miR-125 and STARD13 expression has been described, too.…”
Section: Epigenetics Of Bc and The Role Of Mir-125mentioning
confidence: 99%
“…Its role is well established in BC as well, where it acts as a tumor suppressor gene [ 211 ], regulates cell motility and invasion [ 212 ], endothelial differentiation [ 103 ], metastasis formation [ 213 , 214 ], cell migration [ 215 ], and apoptosis [ 216 ]. It has also been shown that STARD13 exerts its function in BC through its participation in many ceRNETs, such as the one involving a positive TGF-β/miR-9 regulatory loop mediated by the STARD13/YAP axis [ 217 ], the one involving hsa-miR-21-3p [ 218 ], or even the more complex network that involves five different miRs and that controls YAP/TAZ nuclear accumulation and transcriptional activity via modulation of Hippo and Rho-GTPase/F-actin signaling pathways [ 219 ]. A direct link between miR-125 and STARD13 expression has been described, too.…”
Section: Epigenetics Of Bc and The Role Of Mir-125mentioning
confidence: 99%
“…022974) and MMTV-PyMT miR-9 −/− mice were established by Shanghai Southern Model Biotechnology Co., Ltd. (Shanghai, China) using methods described in our previous study. 17 Animal feeding and animal experiment operations were strictly in accordance with the Animal Welfare and Ethics Committee (AWEC) of China Pharmaceutical University. To establish 4T1 tumor-bearing mice, murine breast cancer 4T1 cells (1 × 10 7 ) were inoculated into the ribs and lateral abdominal walls of BALB/c mice to induce tumor formation.…”
Section: Stable Cell Line Constructionmentioning
confidence: 99%
“…The processing method was described in detail in our previous article. 17 In brief, to prepare a single-cell suspension, mouse tissue was stripped and subjected to enzymolysis, filtration, and centrifugation. Then, the red blood cells were lysed and flushed immediately after treatment by flow cytometry sorting (FACS).…”
Section: Flow Cytometry (Facs)mentioning
confidence: 99%
See 1 more Smart Citation
“…Cancer stem cells (CSCs) have emerged as a key focus in cancer research due to their involvement in tumor initiation, progression, and therapy resistance 3,4 . CSCs possess self‐renewal capabilities and exhibit high tumorigenic potential, contributing to tumor recurrence and metastasis 5 . Identifying the molecular mechanisms that regulate CSCs is of paramount importance for developing effective therapeutic strategies against EC.…”
Section: Introductionmentioning
confidence: 99%